Ferroelectric Polarization‐Assisted Sensitive and High‐Power Photodetector in Broad Ultraviolet‐to‐Visible Range. Issue 12 (22nd May 2017) - Liu, Yu; Wang, Jianlin; Huang, Haoliang; Yun, Yu; Meng, Dechao; Yang, Qixin; Zhai, Xiaofang; Fu, Zhengping; Knize, Randy J.; Lu, Yalin
Abstract : Light‐sensitive electronic devices based on semiconductor P–N junctions have been widely used as photodetectors and solar cells. In order to improve the overall performance of such photosensitive devices, new yet simple design is required. In this work, a simple sandwich structure is proposed by combining a new ferroelectric oxide Bi6 FeCoTi3 O18 with graphene. A highly sensitive photodetector is then realized benefiting from the ferroelectric polarization assisted charge separation, as well as from the unique features of graphene such as the extreme sensibility, ballistic transportation, and broadband absorption. The new device has a remarkable on–off response as high as 2 × 10 3 % under a Xe light‐source irradiation. The ferroelectric polarization enhances the photoresponse by about 2 × 10 4 % when compared with a reference sample. Additionally, the new device is sensitive to a wide‐spectrum from visible to ultraviolet, and is tolerant to high power of the incident light. This unique design opens up a new way to develop next‐generation photoelectric devices that can be both proficient and cost effective. Abstract : A graphene/Bi6 FeCoTi3 O18 (BFCTO)/Nb:STO heterostruture is fabricated as a novel photoelectric device. Ferroelectric material BFCTO is used as the photoabsorber, and more importantly, separates the electrons and holes activated under illumination. The separated charges profoundly affect the resistivity of up‐layer graphene. Thus, to measure the resistivity change of graphene, a sensitive response to the incident light is realized.